The Development of Learning Media for Mobile Learning on Virus Contents - Unsya Oktami Jannah; Sri Sukaesih; Muhammad Abdullah (Journal of Biology Education, 2023)
Learning media is a vehicle for distributing messages and learning information which, if designed properly, will greatly help students achieve learning goals. The results of first observations made on students of SMA N 1 Boja, data obtained that only 50% of students remember virus content during X class, and there are more than 90% of students who have and bring Android smartphones to school which should be used for learning. While the results of interviews with biology teachers at SMA N 1 Boja class X, the difficulties in teaching virus content are the absence of teaching aids, content that tends to be abstract and students who tend to memorize rather than understand. Viruses are a content that is difficult to observe because of its form that cannot be seen with the naked eye because of its very small size. Mobile learning media is an innovation of learning media based on Android and information technology (IT) that can be used without the need for an internet connection and can be used anytime and anywhere to learn. Starting from the problem of abstract virus content and its small size so it cannot be seen with the naked eye, and the media used by the teacher is only power point, as well as the potential of students who already have and bring Android smartphones to school but have not been used optimally in learning, it is necessary to develop an android-based learning media, namely mobile learning. Sampling using random sampling technique. In this study using the Pre Experimental Design method with One-Group Pretest-Posttest Design with a sample of class X MIA students at SMA N 1 Boja. The instruments used are: interviews, questionnaires and documentation. Validation was carried out by a biology lecturer at Unnes and a biology teacher at SMA N 1 Boja with a score of >81% (very valid). A small-scale trial was conducted in class XI MIPA 1 with results >91% (effective), while the student and teacher questionnaire responses reached a score of >81%. A large-scale trial was carried out for class X MIPA 4 by conducting a pretest and posttest with classical completeness results >75% (effective). Thus the learning media for mobile learning virus content developed is feasible and effective to be used as a learning resource.